2014
DOI: 10.3917/ctf.052.0041
|View full text |Cite
|
Sign up to set email alerts
|

La transition vers la parentalité des familles homoparentales : recherche et implications cliniques

Abstract: La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écrit de l'éditeur, en dehors des cas prévus par la législation en vigueur en France. Il est précisé que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Finally, several studies identified a series of challenges encountered by same-sex couples in their process toward parenthood, from social stigma and legal biases in the recognition of their suitability as parents, as well as in their recognition as parents, to difficulties in gaining support and validation for their parental goals from the their families of origin and communities [50][51][52][53][54].…”
Section: Motives Desires and Intentions For Parenthood In Lg Peoplementioning
confidence: 99%
“…Finally, several studies identified a series of challenges encountered by same-sex couples in their process toward parenthood, from social stigma and legal biases in the recognition of their suitability as parents, as well as in their recognition as parents, to difficulties in gaining support and validation for their parental goals from the their families of origin and communities [50][51][52][53][54].…”
Section: Motives Desires and Intentions For Parenthood In Lg Peoplementioning
confidence: 99%
“…Past studies have identified a series of challenges for same-sex parents D'Amore & Baiocco, 2014). As Ritenhouse (2011) explained, LGB parents may have to face social stigma or legal biases concerning their suitability as parents or simply be unrecognized as parents because of heteronormativity (the social bias assuming that everyone is heterosexual).…”
Section: Transition To Parenthood For Same-sex Couplesmentioning
confidence: 99%
“…Becoming a parent involves more difficulties and challenges for gay or lesbian couples than it does for heterosexual couples, as same-sex couples experience pressures and prejudice from the social context in which they enter parenthood often in the absence of support from their families of origin (Chabot & Ames, 2004;Ross, 2005). Futhermore these parents need to overcome legal and other costs related to surrogacy and other ARTs that need a level of organization and financial commitment that are generally not required for heterosexual parents (D'Amore & Baiocco, 2014).…”
Section: Transition To Parenthood For Same-sex Couplesmentioning
confidence: 99%